(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Background and Objective Colocasia gigantea is an erect herbaceous perennial tropical root crop of the family Aracea, produced majorly for its underground corms. It is locally called ‘ede nwokuko’ or kochu because of its believed healing power to cure several illnesses. The aim of the research work is to determine the effect of methanolic extract of Colocasia gigantea on the histology of Liver of Male Wistar Rats. Methods Twenty 20 male wistar rats were randomly grouped into four groups of five animals each (n=5) which weighed 160 - 199 gram. Group A, served as control received water and feed throughout the experiment only. Group B, Group C, and Group D received oral administration of 100mg/kg, 250mg/kg and 500mg/kg of methanolic extract, 500 mg/kg of Colocasia gigantea respectively. The administration lasted for 90days. Results Findings from the histological results showed normal hepatocytes and normal portal tracts in both control group and treatment groups B, C, and D. Conclusion The adminstration of methanolic extract of Colocasia gigantea on male wistar rats, showed no toxic effect on the liver.